Comparison of the Effectiveness of Acceptance and Commitment Therapy and Transdiagnostic Treatment on Psychological Distress and Mindfulness in Women with Multiple Sclerosis - Navaei, Mojgan; Fakhri, Mohammad Kazem; Mirzaian, Bahram (Psychology of Woman Journal, 2024)
Objective: The present study aimed to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Transdiagnostic Treatment on psychological distress and mindfulness in patients with Multiple Sclerosis (MS).Methods and Materials: This was a quasi-experimental study with a pretest-posttest and follow-up design, including a control group. The study population consisted of all women aged 20 to 40 with MS who were members of the Amol MS Society during the first six months of 2023. The research sample included 48 individuals with MS, who were selected through convenience sampling and randomly assigned to two experimental groups and one control group. The research instruments included the Kessler Psychological Distress Scale (Kessler, 2002) and the Baer et al. Mindfulness Questionnaire (Baer et al., 2006). Data were analyzed using repeated measures analysis of covariance (ANCOVA) and Bonferroni post hoc tests, with the aid of SPSS software version 24.Findings: The results indicated that there were significant differences between the effects of ACT, Transdiagnostic Treatment, and the control group on the variables of psychological distress and mindfulness (P < 0.05). Moreover, the post hoc test results suggested that Transdiagnostic Treatment had a more substantial therapeutic effect on improving mindfulness in patients with MS compared to ACT. The two-month follow-up demonstrated the stability of the study results.Conclusion: The effectiveness of both approaches suggests that clinicians and treatment teams can mitigate the severity of psychological and emotional symptoms associated with chronic illnesses by integrating psychological treatment approaches alongside biological therapies, thereby facilitating the treatment process.